Should Emerging Markets Worry about U.S. Monetary Policy Announcements? - Gupta, Poonam; Masetti, Oliver; Rosenblatt, David (World Bank, Washington, DC, 2017)
This paper analyzes the spillover effects of U.S. monetary policy announcements on emerging market economies since end-2008, the period coinciding with the use of unconventional policy measures. Monetary policy surprises are measured by changes in two-year Treasury yields in short windows of time around the Federal Reserve Board’s policy announcements. The analysis finds that U.S. monetary policy surprises have a significant impact on emerging economies' exchange rates, equity prices, and bond yields. The impact is larger for surprise tightening of policy than for surprise easing. The impact is disproportionately larger for large surprises, implying that emerging markets are relatively insulated from anticipated policy announcements. The spillover effects of policy announcements of other advanced economies, such as the euro area, Japan, and United Kingdom, are found to be much weaker than those of the United States.